PRINSIP-PRINSIP PEMBELAJARAN BAHASA INDONESIA - Ibrahim Ibrahim (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2008)
Some people argue that the teaching of Indonesian has not been satisfactory in terms of quality and its relevance to students need. In fact, the ability of students to express their idea logically is still considered poor. This is one of issues which needs solution. With regard to this issue, a number of factors should be put under conside-rations including the principle of curriculum, syllabi, approach and method, teaching process, and the principle of teaching Indonesian.